MyKimchi / Amirah Asyikin Azman - Azman, Amirah Asyikin (2021)
MyKimchi provides a high quality of halal homemade Kimchi. Kimchi is Korean’s most famous side dish where they eat it almost every day. Due to the K-Wave/Korean Hallyu in Malaysia, Kimchi demand keep increasing especially for the halal version. Placed in Selangor, this business started their journey on February 2021. MyKimchi is a small business where it is being manage by myself, Amirah Asyikin Binti Azman. I have also created a Facebook account as a way to expand my business. Through this class, I learn how to post for a business such as posting teaser, soft sell and hard sell as well. Besides, MyKimchi emphasize the quality of their products and services as their marketing strategy. MyKimchi offers a high-quality homemade Kimchi with a very affordable price for every customer. Customers at MyKimchi are vary from all age, gender, as well as religion and race. MyKimchi also provides postage and home delivery which offers a great choice especially for our busy customers. We sell a variety types of fresh homemade Kimchi such as Spring Onion Kimchi, Napa Cabbage Kimchi, and Radish Kimchi. Last but not least, I am putting a high commitment promoting my products through social media with a high-quality services and products. Everyone deserves to taste the freshness of these homemade Kimchi.